Synthesis And Anisotropic Properties Of Liquid Crystal Dimers Consisting Of Ester And Disulphide Bridging Groups - Osman, Faridah (2013)
Four new series of dimers consist of ester and disulphide bridging groups have been synthesized and the anisotropic properties for each dimer characterized. These series comprise of two non-symmetric dimers which are α-{4-[(4-substituted-phenylimino)methyl]carbonyl)phenoxy]phenoxy}-ω-[4-(4-(R,S)-2-methylbutyloxy carbonylphenyl)phenoxy]hexanoate, X-E6-RSMB and α-{4-[(4-substituted-phenyl imino)methyl]carbonyl)phenoxy]phenoxy}-ω-[4-(4-(S)-2-methylbutyloxycarbonyl phenyl)phenoxy]hexanoate, X-E6-SMB and also the other two symmetric dimers (6-{4-[(4-substituted-phenylimino)methyl]phenoxy}hexyl)disulphide, X-6-SS-6-X and (6-{4-[(4-bromophenylimino)methyl]phenoxy}alkyl)disulphide, Br-n-SS-n-Br. The differences between the two series of non-symmetric dimers can be attributed to the presence of various terminal substituents and the introduction of chiral and racemic centres at the biphenyl fragments. For both series of symmetrical dimers the differences can be attributed to the variety of the spacer length and terminal substituents.